A hero for WondLa - DiTerlizzi, Tony (DiTerlizzi, Tony. Search for WondLa, 2023)
Raised underground by a robot, twelve-year-old Eva Nine finally finds all she ever wanted in the human colony of New Attica, but something very bad is going on there and unless Eva and her friends stop it, it could mean the end of life on Orbona.